Expression of a maize cell wall hydroxyproline-rich glycoprotein gene in early leaf and root vascular differentiation. - Stiefel, V; Ruiz-Avila, L; Raz, R; Pilar Vallés, M; Gómez, J; Pagés, M; Martínez-Izquierdo, J; Ludevid, MD; Langdale, J; Nelson, T (1990)
The spatial pattern of expression for a maize gene encoding a hydroxyproline-rich glycoprotein (HRGP) was determined by in situ hybridization. During normal development of roots and leaves, the expression of the gene was transient and particularly high in regions initiating vascular elements and associated sclerenchyma. Its expression was also associated with the differentiation of vascular elements in a variety of other tissues. The gene encoded an HRGP that had been extracted from the cell walls of maize suspension culture cells and several other embryonic and post-embryonic tissues. The gene was present in one or two copies in different varieties of maize and in the related monocots teosinte and sorghum. A single gene was cloned from maize using a previously characterized HRGP cDNA clone [Stiefel et al. (1988). Plant Mol. Biol. 11, 483-493]. In addition to the coding sequences for the HRGP and an N-terminal signal sequence, the gene contained a single intron in the nontranslated 3' end.